A MATHEMATICAL APPROACH FOR ANALYSING THE EFFECTS OF CORRUPTION ON TRANSMISSION DYNAMICS OF MALARIA - Julieta Bernadita Adelia Radja; Ariyanto Ariyanto; Ganesha Lapenangga Putra; Meksianis Z Ndii (JURNAL DIFERENSIAL, 2023)
One of the challenges for eradication of infectious diseases is corruption. This may result in an increase in the number of infectious disease cases. In this article, the effect of corruption on the transmission dynamics of malaria is analyzed using a mathematical model. A deterministic model in the form of a system of differential equations is formulated and analyzed. Sensitivity analysis and numerical simulations are also conducted to determine the effect of parameters on the basic reproductive number. The results show that corruption has negative effects on the efforts for reducing the number of malaria cases.